OP24 Clinical efficacy and safety of guselkumab maintenance therapy in patients with moderately to severely active Crohn's Disease: Week 48 analyses from the phase 2 GALAXI 1 study. (21st January 2022) - Danese, S; Panaccione, R; Rubin, D T; Sands, B E; Reinisch, W; D'Haens, G; Panés, J; Gonzalez, S; Weisel, K; Sahoo, A; Frustaci, M E; Yang, Z; et al.
Abstract: Background: GALAXI 1 is a Phase 2, double-blind, placebo (PBO)-controlled, multicenter study evaluating efficacy/safety of guselkumab (GUS), a selective IL-23 p19 antagonist, in patients (pts) with moderately to severely active Crohn's disease (CD) with inadequate response/intolerance to conventional therapies (corticosteroids, immunomodulators) and/or biologics (tumor necrosis factor antagonists, vedolizumab). At Week (Wk) 12, all GUS induction doses (200, 600, and 1200mg IV) had greater improvements vs PBO for key clinical/endoscopic outcomes. We report clinical efficacy and safety of maintenance treatment through Wk48. Methods: GALAXI employed a treat-through design over 48 wks. In induction pts were randomized to GUS 200, 600, or 1200mg IV, ustekinumab (UST) 6mg/kg IV, or PBO IV. Pts transitioned to maintenance dosing as follows: PBO non-responders to UST 6mg/kg IV to 90mg SC q8w, PBO responders to PBO SC q4w, GUS 200mg IV to 100mg SC q8w, GUS 600mg IV to 200mg SC q4w, GUS 1200mg IV to 200mg SC q4w, and UST 6mg/kg IV to 90mg SC q8w. Pts randomized to PBO were not included in Wk48 efficacy analyses. Primary and major secondary endpoints evaluated efficacy of GUS vs PBO at Wk12. Evaluations of Wk48 endpoints were prespecified but not multiplicity controlled. UST was a reference arm; the study was not powered to evaluate differences between treatment groups with respect to efficacy at Wk48. Results: Through Wk48, 248 pts in the primary efficacy analysis set were randomized and evaluated. Baseline demographics were similar across groups (Table 1). Discontinuation rates were low across active treatment groups. No dose response was observed across clinical efficacy assessments (Table 2). Proportions of pts achieving clinical remission at Wk48 ranged from 57.4–73.0% among GUS dose groups. The vast majority of pts in clinical remission were also in corticosteroid-free remission at Wk48; with rates ranging from 55.7–71.4% among GUS dose groups. PRO-2 remission rates ranged from 50.8–69.8%, and proportions of pts achieving clinical response ranged from 67.2–84.1% among GUS dose groups. Proportions of pts achieving abdominal pain scores ≤1 or daily average number of liquid or very soft stools ≤3 are presented in Table 2. Outcomes in the reference UST group are also shown in Table 2. Key safety event rates were similar among GUS dose groups (Table 3); no opportunistic infections, cases of tuberculosis, or deaths were reported in any group. Conclusion: In this treat-through Phase 2 study of pts with moderately to severely active CD, GUS was safe and effective. GUS induction followed by SC maintenance achieved high rates of clinical efficacy at Wk48. Safety results were consistent with the known safety profile in approved indications.